A Novel Architecture of Radio Tracking System Based on Photonics. (January 2016) - Cong, Bo; Jin, Xiaofeng; Yu, Xinfeng
Abstract: We propose a photonics-based novel architecture of radio tracking system in space applications. This system can operate in multiple frequency bands, implement various functions, and realize integrated, generalized, frequency-independent design. This new scheme can meet the needs of future space missions, and especially suitable for space tracking ship.